ANTI-SHARENTING SELEBRITAS: STRATEGI NON-DISCLOSURE DAN ETIKA VISIBILITAS ANAK DI MEDIA SOSIAL - Zephania, Tiara Annisa; Letare, Yolanda Natasia (UNIVERSITAS SARI MUTIARA INDONESIA, 2025)
This conceptual paper critically examines the practice of anti-sharenting among Indonesian celebrities as a deliberate and ethical form of digital privacy management. Focusing on the case of Raisa Andriana and Hamish Daud, who consistently choose not to disclose their child’s identity online despite having a massive public following, this study applies Communication Privacy Management (CPM) theory to analyze the dynamics of non-disclosure, boundary control, and privacy turbulence within family communication. Through a critical review of 42 academic articles and narrative comparison with more performative celebrity families, the paper positions anti-sharenting not as absence or neglect, but as a conscious form of mindful parenting and symbolic resistance against the pressures of algorithmic visibility. The findings highlight how the refusal to expose children on social media can serve as a communicative strategy that prioritizes ethical reflection, child autonomy, and affective responsibility. By reframing invisibility as active agency, this study contributes to expanding sharenting discourse and encourages future research to consider non-visibility as a valid and protective parenting choice in the digital era.